Bantuan Penyuluhan dan Kegiatan Transplantasi Terumbu Karang di Pantai Ketapang Kabupaten Pesawaran - Herison, Ahmad; Romdania, Yuda (Lembaga Penelitian dan Pengabdian Universitas Lampung, 2017)
Abstract — Coral reefs are coastal marine biota biodiversity. Ketapang beach is one of the tourism destinations in the province of Lampung, therefore there are many activities that can be identified damage to the coral reef at the beach area, so that the necessary steps anticipatory one of them is to transplant corals. The purpose of this service activities 1) Knowing the causes of coral reef degradation in Ketapang Beach, 2) Implement saving coral reefs on the coast of Ketapang, Ketapang District of Pesawaran District. The method is performed in the context of community service are 1) Extension to the public on the importance of coral reef ecosystems, 2) Doing tranplastasi coral fragmentation method using acropora seed. Event followed by several stakeholders from the public and the government. This activity can be concluded: 1) The activities of Ketapang beach tourism indicate damage to coral reefs in the region, it is necessary for coral reef conservation efforts with transplant method. 2) The activity of saving coral reefs done by: transplants used is the fragmentation method. And to preserve the coral reef ecosystem, program outreach to the community is also an effort to prevent the destruction of coral reefs. Keywords — Coral Reef, Tranplantation, Ketapang Beach.